Approaches for Measuring Human Capital and Its Effect on Economic Growth in (MENA) Region: A Panel Data Analysis - Lenar N. Safijllin, Fathy E. Y. Abdelmajied (Opción, 2019)
Human capital is a key factor for growth process and competitiveness. This link operates through multiple pathways at the individual, firm and national level. The human capital (education, health) has effects on economic growth through at least three channels: first, it increases in the labor productivity, which leads to increase the output; second, the increase in the productivity leads to high demand for labor therefor output rises because of the number of employed workers increases; third, it leads to an increase in human capital stock attracts physical capital from other countries (foreign investment).Therefore, the main objective of this article is to highlight the approaches of human capital measures and examine the relationship between human capital and GDP per capita (constant 2010 $) in a panel of 15 countries in the MENA region covering from 2008 to 2016 via we apply the latest panel data techniques based on the Ordinary Least Squares (OLS). Findings of panel unit root show that all the variables are stationary of the level and first order. In conclusion, one of the greatest benefits of education and health in the MENA region is GDP per capita.